Core-shell structure composite material based on high-entropy material nanoparticles as well as efficient preparation method and application of core-shell structure composite material

Through the microwave corona discharge auxiliary strategy, the core-shell structure high-entropy material nanoparticles were prepared, which solved the problems of limited applicability, high cost and complex process of the preparation method in the prior art, and achieved efficient and low-cost nanoparticle preparation and performance improvement.

CN119750664APending Publication Date: 2025-04-04HARBIN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411959729.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing nanoparticle preparation methods for high entropy materials have problems such as limited applicability, high equipment costs, complex processes, and difficulty in achieving continuous and efficient preparation and precise structural control.

Method used

Using microwave corona discharge auxiliary strategy, the metal elements that make up high-entropy materials are ultrasonic dispersed in the solvent in the form of metal salts, and are packaged through microwave heating and graphene oxide to achieve the preparation of core-shell structure high-entropy material nanoparticles.

Benefits of technology

The rapid, simple and efficient preparation of high-entropy material nanoparticles is achieved, which reduces the synthesis cost, expands the applicability of the material, optimizes the morphology and structure of the nanoparticles, and improves its performance in the fields of photothermal conversion, electrocatalysis, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750664A_ABST
    Figure CN119750664A_ABST
Patent Text Reader

Abstract

The invention discloses a core-shell structure composite material based on high-entropy material nanoparticles as well as an efficient preparation method and application of the core-shell structure composite material. The invention belongs to the technical field of high-entropy material nanoparticles. The invention aims to solve the technical problems that the applicability is limited, the equipment cost is high, the process is complicated and continuous and efficient preparation and accurate structure control are difficult to realize in the existing high-entropy material nanoparticle preparation method. The method comprises the following steps: preparing metal elements forming the high-entropy material into a precursor solution in the form of metal salt, and then soaking graphene oxide in the precursor solution to obtain metal salt-loaded graphene oxide; and heating the graphene oxide loaded with the metal salt and the metal conductor with the tip in a microwave device, washing after heating, and drying in vacuum to obtain the core-shell structure composite material. And heating the core-shell structure composite material at a high temperature to obtain the high-entropy material nanoparticles. The obtained material is used in the fields of photothermal conversion, electrocatalysis, flexible electronics, biomedical treatment and microelectronic interconnection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of high entropy material nanoparticles, and in particular relates to a core-shell structure composite material based on high entropy material nanoparticles, and an efficient preparation method and application thereof. Background Art

[0002] The existing technology has the following main problems in the synthesis of high entropy material nanoparticles: First, although the synthesis method based on liquid metal can reduce the mixing entropy and achieve mild synthesis, its application range is limited by the liquid metal element, and it is powerless to limit the application field of liquid metal. Secondly, when the solution reduction method is used to deal with a multi-element system, it is difficult to achieve uniform mixing of the components due to the different reduction potentials of each element, resulting in inconsistent particle composition and significant performance impact. In addition, some current advanced technical means, such as carbon thermal shock method, pulsed laser vaporization method and thermal plasma jet method, although they perform well in terms of element inclusion, their equipment is expensive, the operation is complicated, and it is difficult to achieve continuous production, which cannot meet the requirements of industrialization and large-scale preparation. At the same time, these technologies also have deficiencies in the morphology and structural control of nanoparticles, especially in the limited ability to achieve core-shell structure and optimize lattice distortion, which makes it difficult to further improve their performance in the field of photothermal conversion and electrocatalysis. Therefore, the existing technology lacks an innovative method with a wide range of applications, low cost, simple process and continuous and efficient preparation of high entropy alloy nanoparticles, which has become a key issue restricting its industrialization and wide application. Summary of the invention

[0003] The purpose of the present invention is to solve the technical problems of limited applicability, high equipment cost, complex process and difficulty in achieving continuous and efficient preparation and precise structural control in the existing methods for preparing high entropy material nanoparticles, and to provide a core-shell structure composite material based on high entropy material nanoparticles and its efficient preparation method and application.

[0004] One of the purposes of the present invention is to provide an efficient preparation method of a core-shell structure composite material based on high entropy material nanoparticles, the method is carried out according to the following steps:

[0005] S1: Ultrasonic dispersion of metal elements constituting high entropy materials in a solvent in the form of metal salts to obtain a precursor solution, and then immersing graphene oxide in the precursor solution to obtain graphene oxide loaded with metal salts;

[0006] S2: The graphene oxide loaded with metal salt and the metal conductor with a pointed end are placed in a microwave device for heating. After the heating is completed, the graphene oxide and the metal conductor are washed and vacuum dried to obtain a core-shell structured high entropy material nanoparticle@rGO composite material.

[0007] It is further defined that the metal salt in S1 is a chloride or nitrate of a metal.

[0008] It is further defined that the solvent in S1 is at least one of anhydrous ethanol and water.

[0009] It is further defined that the molar content of each metal salt in the precursor solution in S1 is in the range of 5-35%, and the total molar amount satisfies 100%.

[0010] It is further defined that the concentration of each metal salt in the precursor solution in S1 is 0.01-1 mol / L.

[0011] It is further defined that the metal conductor with a pointed end in S2 is a copper sheet, a copper mesh, a copper wire or a syringe needle.

[0012] It is further defined that the graphene oxide loaded with metal salt in S2 is in contact with the metal conductor having a pointed end.

[0013] It is further defined that the microwave power in S2 is 750-3000 W and the time is 5-30 s.

[0014] It is further defined that in S2, water and anhydrous ethanol are used for alternating washing, each washing is performed 3 times.

[0015] The second object of the present invention is to provide a core-shell structure composite material prepared according to the above method, wherein the shell layer is reduced graphene oxide and the core is high entropy material nanoparticles.

[0016] It is further defined that the particle size of the nanoparticles is 25-45 nm.

[0017] The third object of the present invention is to provide a method for preparing high entropy material nanoparticles, the method comprising:

[0018] S1: Ultrasonic dispersion of metal elements constituting high entropy materials in a solvent in the form of metal salts to obtain a precursor solution, and then immersing graphene oxide in the precursor solution to obtain graphene oxide loaded with metal salts;

[0019] S2: The graphene oxide loaded with metal salt and the metal conductor with a sharp tip are placed in a microwave device for heating, and after heating, they are washed and vacuum dried to obtain a core-shell structure high entropy material nanoparticle@rGO composite material;

[0020] S3: The core-shell structure high entropy material nanoparticles@rGO composite material obtained in S2 is subjected to high-temperature heating to remove rGO, thereby obtaining high entropy material nanoparticles.

[0021] It is further defined that the metal salt in S1 is a chloride or nitrate of a metal.

[0022] It is further defined that the solvent in S1 is at least one of anhydrous ethanol and water.

[0023] It is further defined that the molar content of each metal salt in the precursor solution in S1 is in the range of 5-35%, and the total molar amount satisfies 100%.

[0024] It is further defined that the concentration of each metal salt in the precursor solution in S1 is 0.01-1 mol / L.

[0025] It is further defined that the metal conductor with a pointed end in S2 is a copper sheet, a copper mesh, a copper wire or a syringe needle.

[0026] It is further defined that the graphene oxide loaded with metal salt in S2 is in contact with the metal conductor having a pointed end.

[0027] It is further defined that the microwave power in S2 is 750-3000 W and the time is 5-30 s.

[0028] It is further defined that in S2, water and anhydrous ethanol are used for alternating washing, each washing is performed 3 times.

[0029] It is further defined that the high temperature heating in S3 is performed at a temperature of 800-1200° C. and a time of 10-30 min.

[0030] A fourth object of the present invention is to provide a high entropy alloy nanoparticle obtained by the above method, wherein the high entropy alloy nanoparticle is prepared using metal chloride as a raw material in an inert atmosphere.

[0031] A fifth object of the present invention is to provide a high entropy oxide nanoparticle obtained by the above method, wherein the high entropy oxide nanoparticle is prepared using metal chloride as a raw material.

[0032] The sixth object of the present invention is to provide a high entropy nitride nanoparticle obtained by the above method, wherein the high entropy nitride nanoparticle is prepared using metal nitrate as a raw material.

[0033] The seventh object of the present invention is to provide high entropy sulfide nanoparticles obtained according to the above method, wherein the high entropy sulfide nanoparticles are prepared using metal chloride as a raw material and by adding sulfuric acid to a precursor solution.

[0034] It is further defined that the concentration of concentrated sulfuric acid in the precursor solution is 15-20 mol / L.

[0035] The eighth object of the present invention is to provide an application of the above-mentioned core-shell structure high entropy material nanoparticles@rGO composite materials or high entropy material nanoparticles in the fields of photothermal conversion, electrocatalysis, flexible electronics, biomedicine, and microelectronic interconnection.

[0036] Compared with the prior art, the present invention has the following significant effects:

[0037] The present invention proposes a novel synthesis method for preparing high entropy alloy nanoparticles and core-shell structure composite materials based on the high entropy alloy nanoparticles. The high entropy material nanoparticles can be synthesized quickly, simply and efficiently by microwave corona discharge. The method is particularly suitable for preparing high entropy alloy nanoparticles (HEANPs) and high entropy oxide nanoparticles (HEONPs) with a core-shell structure, and can be extended to the preparation of high entropy sulfides and nitrides.

[0038] The microwave corona discharge assisted strategy of the present invention overcomes the shortcomings of high equipment cost and complex process of traditional methods, has low microwave power requirement, short reaction time, and significantly reduces the synthesis cost. The precise design of the core-shell structure is achieved through matrix regulation, and the photothermal and electrocatalytic performance are optimized. It can be extended to the preparation of a variety of high entropy materials, including alloys, oxides, sulfides and nitrides, and has wide applicability. The rapid preparation and composition homogenization of nanoparticles are achieved. The prepared materials have broad application prospects in the fields of photothermal conversion, electrocatalysis, flexible electronics, biomedicine, microelectronic interconnection, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 Schematic diagram of the process and mechanism of preparing high entropy material nanoparticles by microwave corona discharge of the present invention; wherein, (a) schematic diagram of the excitation process, (b) real image of microwave corona discharge excitation, (c) schematic diagram of the formation mechanism of high entropy material nanoparticles;

[0040] Figure 2 Transmission electron microscopy characterization and EDS image of AlCoCrFeNi HEO NPs@rGO obtained in step (3) of Example 1; wherein (a) -TEM, (b) -HRTEM, (c) -SAED, (d) -HAADF STEM, (e) -SAED mode, (f) -EDS;

[0041] Figure 3 Transmission electron microscopy characterization and EDS graph of AlCrFeNi HEO NPs obtained in step (4) of Example 1; wherein (a) is low-magnification bright field TEM, (b) is high-magnification bright field TEM, (c) is the SAED pattern corresponding to (b), and (d) is a dark field TEM image and EDS spectrum;

[0042] Figure 4 Transmission electron microscopy characterization and EDS image of AlCoCrFeNi HENNPs obtained in step (4) of Example 2;

[0043] Figure 5 Transmission electron microscopy characterization and EDS image of AlCoCrFeNi HES NPs obtained in step (4) of Example 3;

[0044] Figure 6The effects of the excitation source type and the ethanol-water ratio on the excitation time of the high-temperature plasma environment formed by microwave corona discharge in Example 1 and Examples 5-6;

[0045] Figure 7 The UV-Vis-NIR absorption spectra of the nanoparticles obtained in Example 1 and Example 4. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0047] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0048] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.

[0049] When equivalent, concentration or other value or parameter is represented by the range limited by range, preferred range or a series of upper preferred value and lower preferred value, this should be understood as specifically disclosing all ranges formed by any pairing of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether the scope is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the scope is intended to include its end value and all integers and fractions within the scope. In the present application specification and claims, range limitation can be combined and / or interchanged, if these ranges are not otherwise stated, include all sub-ranges contained therein.

[0050] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.

[0051] The "one embodiment" or "embodiment" of the present invention refers to a specific feature, structure or characteristic that can be included in at least one implementation of the present invention. The "in one embodiment" that appears in different places in this specification does not refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.

[0052] The endpoints and any values ​​of the ranges disclosed in the invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.

[0053] Embodiment 1:

[0054] The efficient preparation method of high entropy oxide nanoparticles and core-shell structure composite materials based on the high entropy oxide nanoparticles of this embodiment is carried out according to the following steps:

[0055] (1) AlCl3, CrCl3·6H2O, CoCl2·6H2O, FeCl3, and NiCl2·2H2O were added simultaneously into 20 mL of anhydrous ethanol at a concentration of 0.1 mol / L to obtain a precursor solution.

[0056] (2) The precursor solution was magnetically stirred at 1000 r / min for 20 min before use, and then the graphene oxide was immersed in the metal salt solution. The graphene oxide was then taken out and placed in a flask together with a rectangular metal copper sheet (1 cm×2 cm). The metal copper sheet was covered on the graphene oxide sheet loaded with the metal salt and heated under a 900 W microwave for 15 s.

[0057] (3) After the microwave heating, the reduced graphene oxide material was taken out, washed alternately with water and anhydrous ethanol for three times, and then dried under vacuum at room temperature for 12 h to obtain a core-shell structured high entropy oxide nanoparticles@rGO composite material, referred to as AlCoCrFeNi HEONPs@rGO. The TEM and EDS images of the obtained AlCoCrFeNi HENNPs@rGO are shown in Figure 2 As shown, Figure 2 As shown in a and 2b, the core-shell structure is visible with clear graphene oxide encapsulation. High-resolution transmission electron microscopy (HRTEM) images and Fourier transform diffraction patterns ( Figure 2 b, 2c) confirmed that the synthesized nanoparticles present a single-phase solid solution with a face-centered cubic (FCC) structure and a distinct carbon layer on the surface. Energy dispersive spectroscopy (EDS) showed that the elements aluminum (Al), chromium (Cr), cobalt (Co), iron (Fe), nickel (Ni) and oxygen (O) were uniformly distributed throughout the sample and at the level of individual particles ( Figure 2 d). Taken together, these findings confirm that AlCoCrFeNi HEO@rGO core-shell nanoparticles have been successfully synthesized ( Figure 2 df).

[0058] (4) The AlCoCrFeNi HEO NPs@rGO was heated at 1000°C for 20 min to remove rGO and obtain high entropy oxide nanoparticles, referred to as AlCoCrFeNi HEO NPs. The TEM and EDS images of the obtained AlCoCrFeNi HEONPs are shown in Figure 3 As shown, Figure 3 As shown in a and 3b, no carbon element was observed after sintering, and the nanoparticles were evenly distributed without obvious agglomeration. Fourier transform diffraction spectrum ( Figure 3 c, 3d) and energy spectrum structure confirmed that the synthesized nanoparticles presented a single-phase solid solution with a face-centered cubic (FCC) structure, realizing the production of non-core structured high-entropy alloy oxide nanoparticles.

[0059] Embodiment 2:

[0060] The efficient preparation method of high entropy nitride nanoparticles and core-shell structure composite materials based on the high entropy nitride nanoparticles of this embodiment is carried out in the following steps:

[0061] (1) Al(NO3)3, Cr(NO3)3·6H2O, Co(NO3)2·6H2O, Fe(NO3)3, and Ni(NO3)2·2H2O were added simultaneously into 20 mL of anhydrous ethanol at a concentration of 0.1 mol / L to obtain a precursor solution.

[0062] (2) The precursor solution was magnetically stirred at 1000 r / min for 20 min before use, and then the graphene oxide was immersed in the metal salt solution. The graphene oxide was then taken out and placed in a flask together with a rectangular metal copper sheet (1 cm×2 cm). The metal copper sheet was covered on the graphene oxide sheet loaded with the metal salt and heated under a 900 W microwave for 15 s.

[0063] (3) After the microwave heating, the reduced graphene oxide material was taken out, washed alternately with water and anhydrous ethanol for three times, and then vacuum dried at room temperature for 12 hours to obtain a core-shell structured high entropy nitride nanoparticles@rGO composite material, referred to as AlCoCrFeNi HENNPs@rGO. Its TEM image and EDS image are shown in Figure 4 As shown, the figure shows that Al, Co, Cr, Fe, Ni, and S elements are evenly distributed inside the particles.

[0064] Embodiment 3:

[0065] The efficient preparation method of high entropy sulfide nanoparticles and core-shell structure composite materials based on the high entropy sulfide nanoparticles of this embodiment is carried out according to the following steps:

[0066] (1) AlCl3, CrCl3·6H2O, CoCl2·6H2O, FeCl3, and NiCl2·2H2O were added to 20 mL of anhydrous ethanol at a concentration of 0.1 mol / L, and 0.11 mL of 98% concentrated sulfuric acid (18.4 mol / L) was added dropwise thereto to obtain a precursor solution.

[0067] (2) The precursor solution was magnetically stirred at 1000 r / min for 20 min before use, and then the graphene oxide was immersed in the metal salt solution. The graphene oxide was then taken out and placed in a flask together with a rectangular metal copper sheet (1 cm×2 cm). The metal copper sheet was covered on the graphene oxide sheet loaded with the metal salt and heated under a 900 W microwave for 15 s.

[0068] (3) After the microwave heating, the reduced graphene oxide material was taken out, washed alternately with water and anhydrous ethanol for three times, and then vacuum dried at room temperature for 12 hours to obtain a core-shell structured high entropy sulfide nanoparticles@rGO composite material, referred to as AlCoCrFeNi HES NPs@rGO. Its TEM image and EDS image are shown in Figure 2. Figure 5 As shown, the figure shows that Al, Co, Cr, Fe, Ni, and S elements are evenly distributed inside the particles.

[0069] Embodiment 4:

[0070] The efficient preparation method of high entropy oxide nanoparticles and core-shell structure composite materials based on the high entropy oxide nanoparticles of this embodiment is carried out according to the following steps:

[0071] (1) GaCl3, AlCl3, CrCl3·6H2O, CoCl2·6H2O, FeCl3, and NiCl2·2H2O were added simultaneously into 20 mL of anhydrous ethanol at a concentration of 0.1 mol / L to obtain a precursor solution.

[0072] (2) The precursor solution was magnetically stirred at 1000 r / min for 20 min before use, and then the graphene oxide was immersed in the metal salt solution. The graphene oxide was then taken out and placed in a flask together with a rectangular metal copper sheet (1 cm×2 cm). The metal copper sheet was covered on the graphene oxide sheet loaded with the metal salt and heated under a 900 W microwave for 15 s.

[0073] (3) After the microwave heating, the reduced graphene oxide material was taken out, washed alternately with water and anhydrous ethanol for three times, and then vacuum dried at room temperature for 12 h to obtain a core-shell structured high entropy oxide nanoparticles@rGO composite material, referred to as GaAlCoCrFeNi HEO NPs@rGO.

[0074] (4) GaAlCoCrFeNi HEONPs@rGO was heated at 1000°C for 20 min to remove rGO and obtain high entropy oxide nanoparticles, referred to as GaAlCoCrFeNi HEO NPs.

[0075] Embodiment 5:

[0076] The difference between this embodiment and embodiment 1 is that: in step (2), the copper sheet is replaced by a 500-mesh copper mesh, a copper wire, and a syringe needle, respectively, and the microwave power is 750 W. The other steps and parameters are the same as those in embodiment 1.

[0077] Embodiment 6:

[0078] The difference between this embodiment and embodiment 1 is that: in step (1), the solvent is replaced by a mixed solvent and pure water with a volume ratio of ethanol to water of 80:20, 60:40, 40:60, and 20:80, respectively. In step (2), the microwave power is 750 W. The other steps and parameters are the same as those in embodiment 1.

[0079] Test example 1:

[0080] The effects of the excitation source type and the ethanol-water ratio on the excitation time of microwave corona discharge to form a high-temperature plasma environment. Figure 6 As shown in the figure, the effect of different excitation sources (copper sheet, copper mesh, copper wire, syringe needle) on the excitation time and the effect of ethanol-water ratio on the excitation time are depicted. Figure 6 It can be seen that all kinds of excitation sources can achieve the excitation of microwave plasma with high efficiency. Among them, the copper mesh with the most metal tips has the shortest excitation time, followed by copper sheet, copper wire and syringe needle. As the ethanol content increases, the excitation time of the metal copper sheet gradually increases, but all can achieve excitation.

[0081] Test example 2:

[0082] The photothermal conversion efficiencies of the original graphene oxide, the AlCoCrFeNi HEO NPs@rGO and AlCoCrFeNi HEO NPs obtained in steps (3) to (4) of Example 1, and the GaAlCoCrFeNi HEO NPs and GaAlCoCrFeNi HEO NPs@rGO obtained in steps (3) to (4) of Example 4 were tested under the entire solar spectrum. The results are as follows: Figure 7As shown, the results show that the high entropy nanomaterials prepared by the present invention have a photothermal conversion efficiency far exceeding that of the original GO, among which the best performing AlCoCrFeNi HEONPs@rGO is close to a photothermal conversion efficiency of more than 90% in the entire solar spectrum (280nm-2500nm).

[0083] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. An efficient preparation method of a core-shell structure composite material based on high entropy material nanoparticles, characterized in that: The method: S1: Ultrasonic dispersion of metal elements constituting high entropy materials in a solvent in the form of metal salts to obtain a precursor solution, and then immersing graphene oxide in the precursor solution to obtain graphene oxide loaded with metal salts; S2: The graphene oxide loaded with metal salt and the metal conductor with a pointed end are placed in a microwave device for heating. After the heating is completed, the graphene oxide and the metal conductor with a pointed end are washed and vacuum dried to obtain a core-shell structured high entropy material nanoparticle@rGO composite material.

2. The method according to claim 1, characterized in that: The metal salt in S1 is a chloride or nitrate of a metal, the solvent is at least one of anhydrous ethanol and water, the molar content of each metal salt in the precursor solution is in the range of 5-35%, the total molar amount satisfies 100%, and the concentration of each metal salt in the precursor solution is 0.01-1 mol / L; the metal conductor with a pointed tip in S2 is a copper sheet, a copper mesh, a copper wire or a syringe needle, the microwave power is 750-3000 W, and the time is 5-30s.

3. The core-shell structure composite material obtained by the method according to claim 2, characterized in that: The shell is reduced graphene oxide and the core is high entropy material nanoparticles.

4. A method for preparing high entropy material nanoparticles, characterized in that: The method: S1: Ultrasonic dispersion of metal elements constituting high entropy materials in a solvent in the form of metal salts to obtain a precursor solution, and then immersing graphene oxide in the precursor solution to obtain graphene oxide loaded with metal salts; S2: The graphene oxide loaded with metal salt and the metal conductor with a sharp tip are placed in a microwave device for heating, and after heating, they are washed and vacuum dried to obtain a core-shell structure high entropy material nanoparticle@rGO composite material; S3: The core-shell structure high entropy material nanoparticles@rGO composite material is heated at high temperature to remove rGO, thereby obtaining high entropy material nanoparticles.

5. The high entropy alloy nanoparticles obtained by the method according to claim 4, characterized in that: It is prepared in an inert atmosphere using metal chloride as raw material.

6. The high entropy oxide nanoparticles obtained by the method of claim 4, characterized in that: It is prepared from metal chlorides.

7. The high entropy nitride nanoparticles obtained by the method of claim 4, characterized in that: It is prepared from metal nitrates.

8. The high entropy sulfide nanoparticles obtained by the method of claim 4, characterized in that: It is prepared by using metal chloride as raw material and adding sulfuric acid to the precursor solution.

9. The nanoparticle according to claim 8, characterized in that The concentration of concentrated sulfuric acid in the precursor solution is 15-20 mol / L.

10. Application of the core-shell structure high entropy material nanoparticle@rGO composite material described in claim 3 or the high entropy material nanoparticles described in any one of claims 5 to 9 in the fields of photothermal conversion, electrocatalysis, flexible electronics, biomedicine, and microelectronic interconnection.